2016
DOI: 10.1007/978-3-319-39583-8_32
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Gamification Strategies Rooted in Self-Determination Theory for Social Adaptive E-Learning

Abstract: (2016) 'Motivational gamication strategies rooted in self-determination theory for social adaptive E-Learning. ', in Intelligent Tutoring Systems, 13th International Conference, ITS 2016, Zagreb, Croatia, June 7-10, 2016 Further information on publisher's website:http://dx.doi.org/10.1007/978-3-319-39583-8 3 2Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/978-3-319-39583-832Additional information: Use policyThe full-text may be used and/or reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 10 publications
2
37
0
1
Order By: Relevance
“…The latter has been successfully applied in several studies e.g. [33,32,37] to design motivational gamification strategies towards an adaptive gamification approach [2].…”
Section: Theoretical Background and Related Work On Gamification Frammentioning
confidence: 99%
See 2 more Smart Citations
“…The latter has been successfully applied in several studies e.g. [33,32,37] to design motivational gamification strategies towards an adaptive gamification approach [2].…”
Section: Theoretical Background and Related Work On Gamification Frammentioning
confidence: 99%
“…Change the state of the user refers to altering the end-user attitude towards their goals, motivation and beliefs and aligning them with the benefits of using the system [32,38]. Support of Learning refers to adaptive solutions supporting the end-users in their learning process [36].…”
Section: Structure and Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant research from other contexts can be found. Shi and Cristea [53] propose motivational gamification strategies based on self-determination theory for an e-learning context. In testing the strategies, they found most success with supporting students' competence, least for supporting relatedness.…”
Section: Research Area and Research Questionmentioning
confidence: 99%
“…The players should get recognitions for actions that matter to them. [24] The three SDT needs have great influence in three motivations: perceived usefulness, perceived enjoyment and perceived ease of use. In SDT, perceived usefulness is a form of extrinsic motivation while perceived enjoyment a form of intrinsic motivation.…”
Section: Relatednessmentioning
confidence: 99%